2020
DOI: 10.1177/2325967120913531
|View full text |Cite
|
Sign up to set email alerts
|

Medial Opening Wedge High Tibial Osteotomy Decreases Medial Meniscal Extrusion and Improves Clinical Outcomes and Return to Activity

Abstract: Background: Medial meniscal extrusion (MME) is defined as displacement of the meniscus that extends beyond the tibial margin. Knee varus malalignment increases MME. Purpose/Hypothesis: The purpose of this study was to quantify MME before and after medial opening wedge high tibial osteotomy (HTO) and to correlate the reduction of MME with clinical outcomes and return to activity. It was hypothesized that MME would decrease after HTO and that patients with lower MME after surgery would have improved clinical out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…High tibial osteotomy (HTO) is a widely used and well-established effective surgical treatment which aims to correct the varus malalignment or deformation with compartmental osteoarthritis or osteonecrosis of the knee in both young and elderly patients [ 1 ]. HTO is intended to shift the misaligned mechanical axis to the midline of the knee to restore normal limb alignment, thereby minimizing the load on the medial compartment to slow down the osteoarthritis progression [ 2 – 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…High tibial osteotomy (HTO) is a widely used and well-established effective surgical treatment which aims to correct the varus malalignment or deformation with compartmental osteoarthritis or osteonecrosis of the knee in both young and elderly patients [ 1 ]. HTO is intended to shift the misaligned mechanical axis to the midline of the knee to restore normal limb alignment, thereby minimizing the load on the medial compartment to slow down the osteoarthritis progression [ 2 – 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Promisingly, many studies have demonstrated that knee pain could be relieved by open wedge high tibial osteotomy (OWHTO) 9-12 . OWHTO is an effective procedure for patients with medial unicompartmental KOA [13][14][15][16] . In a study conducted by Astur et.al, 66 patients who underwent OWHTO were reviewed, The postoperative scores, including Knee Injury and Osteoarthritis Outcome Score (KOOS), visual analog scale (VAS), and Tegner scores were higher than those found preoperative 17 . In a study conducted by Altay et.al, 34 patients who underwent OWHTO were reviewed, VAS scores improved signi cantly from preoperative 53.71 ± 10.02 to postoperative 14.12 ± 6.08, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores improved signi cantly from preoperative 57.34 ± 6.37 to postoperative 31.94 ± 5.12 18 .…”
Section: Introductionmentioning
confidence: 93%
“…However, patients cannot engage in strenuous exercise after TKA, and the prosthesis has a certain number of years of use. For young patients, the surgical effect is limited and the risk of surgical failure increases [ 2 , 3 ]. Thus, TKA is too aggressive and HTO is an ideal choice for younger patients who have a high demand for activity and are confined to medial compartment osteoarthritis of the knee combined with varus deformity [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…HTO is generally suitable for patients younger than 60 years old, with limited medial compartment osteoarthritis, no obvious wear on the tibiofemoral and patellofemoral articular surfaces, tibial varus deformity between 5° and 20°, and high demand for postoperative activity [ 7 , 8 ]. It has been reported that some athletes can return to the arena after HTO [ 2 ].…”
Section: Introductionmentioning
confidence: 99%